ONLINE SHOPPING REGISTERS ON SOCIAL MEDIA APPLICATIONS (REGISTER JUAL BELI ONLINE PADA APLIKASI MEDIA SOSIAL) - Wenny Noorahim (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2018)
AbstractOnline Shopping Registers on Social Media Applications. Registers is a variation of language used ina particular field in which applied in the use of selling and purchasing transaction language. Therefore,this study examines (1) the process of morphology registers in online shopping, (2) the registers syntaxstructure in online shopping, and (3) the variations of registers stylistic form in the online shopping onsocial media application. This research uses qualitative descriptive approach. Data and source of data ofthis research is in a written speech form which taken from sellers and buyers who communicate duringonline shopping transaction. Data collection technique uses observation method through intensivereading and writing techniques. Data analysis techniques of this research are through three steps suchas reduction data, presentation data and conclusion. The results obtained are as follows. First, themorphology process found in the registers includes (1) affixation, (2) reduplication, (3) composition, and(4) abbreviation. Second, the syntactic structure found in the register is in the form of ellipsis sentenceswith the subject delegation, predicate and subject with predicate. Third, the form of stylistic variationsfound in the registers include (1) code mixing, (2) interference, and (3) the use of casual variety.Key words: registers, registers morphology, registers syntax, variations of registers stylisticAbstrakRegister Jual Beli Online pada Aplikasi Media Sosial. Register merupakan variasi bahasa yangdigunakan dalam bidang tertentu yang salah satunya penggunaan bahasa dalam jual beli. Olehsebab itu, penelitian ini mengkaji tentang (1) proses morfologis register jual beli online, (2) struktursintaksis register jual beli online, dan (3) wujud variasi stilistik register jual beli online pada beberapaaplikasi media sosial. Peneltian ini menggunakan pendekatan deskriptif kualitatif. Data dan sumberdata penelitian ini ialah tuturan tertulis dari penjual dan pembeli yang berkomunikasi selama prosesjual beli online berlangsung. Teknik pengumpulan data menggunakan metode simak melalui teknikpembacaan intensif dan pencatatan. Teknik analisis data melalui langkah reduksi data, penyajian datadan penarikan kesimpulan. Hasil penelitian yang diperoleh adalah sebagai berikut. Pertama, prosesmorfologis yang ditemukan meliputi; (1) afiksasi, (2) reduplikasi, (3) komposisi, dan (4) abreviasi.Kedua, struktur sintaksis yang ditemukan berupa kalimat elipsis dengan pelesapan subjek, predikatserta subjek dan predikat. Ketiga, wujud variasi stilistik yang ditemukan meliputi; (1) campur kode, (2)interferensi, dan (3) penggunaan ragam santai.Kata-kata kunci: register, morfologis register, sintaksis register, variasi stilistik register